FreeHand 9 authorized / [Tony Roame, author and instructional designer]. - Roame, Tony.; Macromedia (Firm) (Berkeley, CA : Macromedia Press, 2000)
An object-oriented drawing program, for designing, page layout, and animated Web graphics.
CD-ROM includes practice files for all 10 lessons & QuickTime movies to demonstrate specific techniques.
Book is accompanied by 1 CD, entitled'Freehand 9 authorized' bearing the same call number and available at Bahagian Koleksi Media
Includes bibliographical references and index.
System requirements for CD-ROM: Microsoft Windows 95/98/2000/NT; Intel Pentium or faster; 64MB RAM; 70MB+ disk space; PostScript printer; Web browser.
System requirements for CD-ROM: PowerMacintosh; Mac OS 8.1 or later; 64MB+ RAM; 50MB+ disk space; PostScript printer; Web browser.
Keywords: FreeHand (Computer file); Computer graphics; Web sites -- Design